Satisfaction and Trust as Predictors of Customer Loyalty: An Empirical Study in the Lighting Distribution Industry - Juniaman Zalukhu; Rifqah Harahap; Hafni Cholida Nasution (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: In late 2024, PT. Cahaya Prima Lestari Abadi (Philips Lighting) experienced a noticeable decline in customer numbers. This downturn was attributed to several service-related issues, including employee performance that failed to meet customer expectations, resulting in dissatisfaction, as well as incidents of product damage during delivery, which undermined customer trust. These conditions collectively indicated weakening customer satisfaction and trust, ultimately affecting customer loyalty. This study aims to analyze the influence of customer satisfaction and customer trust on customer loyalty within PT. Cahaya Prima Lestari Abadi. Materials and methods: A quantitative research approach was employed. The study population consisted of 158 customers, and a sample of 61 respondents was selected through random sampling using the Slovin formula. Data were gathered through observations, interviews, questionnaires, and documentation. Multiple linear regression analysis was conducted using SPSS version 25 to examine the effects of customer satisfaction and customer trust on customer loyalty. Results: The findings revealed that customer satisfaction and customer trust both exert a positive and significant influence on customer loyalty. The resulting regression equation was Y = 6.104 + 0.446X₁ + 0.301X₂ + E. The t-test results showed that the satisfaction variable was significant (tcount = 3.506 > ttable = 2.001; p = 0.001), as was the trust variable (tcount = 2.984 > ttable = 2.001; p = 0.004). The F-test further confirmed a significant simultaneous effect (Fcount = 67.007 > Ftable = 3.16). The coefficient of determination (R² = 0.688) indicated that 68.8% of the variance in customer loyalty was explained by customer satisfaction and customer trust, while the remaining 31.2% was attributable to other factors not included in the model. Conclusions: The study concludes that both customer satisfaction and customer trust play crucial roles in shaping customer loyalty. Improving service quality and reducing delivery-related risks are essential strategies to strengthen loyalty and stabilize customer engagement. Future research should investigate additional determinants that may influence customer loyalty beyond satisfaction and trust.